The Role of Innate and Adaptive Immune Cells in the Immunopathogenesis of Chronic Obstructive Pulmonary Disease - Nurwidya, Fariz (Tuberc Respir Dis (Seoul), 2016)
Chronic obstructive pulmonary disease (COPD) is a chronic and progressive inflammatory disease of the airways and lungs that results in limitations of continuous airflow and is caused by exposure to noxious gasses and particles. A major cause of morbidity and mortality in adults, COPD is a complex disease pathologically mediated by many inflammatory pathways. Macrophages, neutrophils, dendritic cells, and CD8+ T-lymphocytes are the key inflammatory cells involved in COPD. Recently, the non-coding small RNA, micro-RNA, have also been intensively investigated and evidence suggest that it plays a role in the pathogenesis of COPD. Here, we discuss the accumulated evidence that has since revealed the role of each inflammatory cell and their involvement in the immunopathogenesis of COPD. Mechanisms of steroid resistance in COPD will also be briefly discussed.